Generation of luciferase-expressing Leishmania infantum chagasi and assessment of miltefosine efficacy in infected hamsters through bioimaging. - Juliana Q Reimão; Jordana C Oliveira; Cristiana T Trinconi; Paulo C Cotrim; Adriano C Coelho; Silvia R B Uliana (Public Library of Science (PLoS), 2015)
The only oral drug available for the treatment of leishmaniasis is miltefosine, described and approved for visceral leishmaniasis in India. Miltefosine is under evaluation for the treatment of cutaneous leishmaniasis in the Americas although its efficacy for the treatment of human visceral leishmaniasis caused by Leishmania infantum chagasi has not been described. Drug efficacy for visceral leishmaniasis is ideally tested in hamsters, an experimental model that mimics human disease. Luciferase has been validated as a quantitative tool for the determination of parasite burden in experimental leishmaniasis. However, there are no reports of luciferase detection in the model of progressive visceral leishmaniasis in hamsters. Therefore, the aims of this study were to generate recombinant Leishmania infantum chagasi expressing the luciferase gene (Lc-LUC), characterize the biological properties of this transgenic line as compared with the wild-type parasites and evaluate miltefosine effectiveness in Lc-LUC infected hamsters.A transgenic line containing a luciferase encoding gene integrated into the ribosomal DNA locus was obtained and shown to produce bioluminescence which correlated with the number of parasites. Lc-LUC growth curves and susceptibility to pentavalent antimony and miltefosine in vitro were indistinguishable from the wild-type parasites. The effectiveness of pentavalent antimony was evaluated in Lc-LUC infected hamsters through bioimaging and determination of Leishman Donovan Units. Both methods showed concordant results. Miltefosine was effective in the treatment of Lc-LUC-infected hamsters, as demonstrated by the reduction in parasite burden in a dose-dependent manner and by prolongation of animal survival.Luciferase expressing parasites are a reliable alternative for parasite burden quantification in hamsters with advantages such as the possibility of estimating parasite load before drug treatment and therefore allowing distribution of animals in groups with equivalent mean parasite burden. Miltefosine was effective in vivo in an L. infantum chagasi experimental model of infection.